ANALISIS LOKASI, KERAGAMAN PRODUK, KUALITAS PELAYANAN DAN KEPUTUSAN PEMBELIAN PADA USAHA KECIL RUMAH MAKAN PADANG DI KOTA SEMARANG - Muhammad Ryan Darmawan; Ari Pradhanawati (Universitas Diponegoro, 2016)
Padang restaurant is a restaurant business that sells and serves various culinary or minang Kabau dish originating from West Sumatra. Restaurant business Padang many newly been established both in the scale of micro, small, medium and large in Indonesia, especially in the Semarang city. Increasing number of business also will be increasing fierce competition. Business owners should have a strategy in the factor - factor of location, diversity of products, Quality of Service, and how consumer responses and reasons in making purchasing decisionsThe data were collected by using an overview of the field, observation, interviews, documents gathering, and literatures, and been analyzed by the case study method. The results showed that the location, product diversity, and quality of service that is owned by Padang restaurant in the city of Semarang has been good enough and strategic adjustable with theory and research that has been done before. In a purchase decision, consumers pay attention to all the factors of every Padang restaurant, and consumers prefer to loyal factor in the diversity of products owned by Padang restaurant. With a variety of advantages, it is recommended to small business of Padang restaurant owners in order to maintain the advantages, and make location improvements and make an innovation either for their products and the estabilished services.